Kinetics of Bacterial Adaptation, Growth, and Death at Didecyldimethylammonium Chloride sub-MIC Concentrations - Pedreira, Adrián; Vázquez, José A.; García, Míriam R. (Frontiers in Microbiology, 2022)
Minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) are standard indexes for determining disinfection effectiveness. Nevertheless, they are static values disregarding the kinetics at sub-MIC concentrations where adaptation, growth, stationary and death phases can be observed. The understanding of these dynamic mechanisms is crucial to designing effective disinfection strategies. In this work, we studied the 48 hours kinetics of Bacillus cereus and Escherichia coli cells exposed to sub-MIC concentrations of didecyldimethylammonium chloride (DDAC). Two mathematical models were employed to reproduce the experiments: the only-growth classical logistic model and a mechanistic model including growth and death dynamics. Although both models reproduce the lag, exponential and stationary phases, only the mechanistic model is able to reproduce the death phase and reveals the concentration dependence of the bactericidal/ bacteriostatic activity of DDAC. This model could potentially be extended to study other antimicrobials and reproduces changes in optical density and colony-forming units with the same parameters and mechanisms of action.